Formation of a functional homo-junction interface through ZnO atomic layer passivation: Enhancement of carrier mobility and threshold voltage in a ZnO nanocrystal field effect transistor - Kim, Youngjun; Chang, Mincheol; Cho, Seongeun; Kim, Minkyong; Kim, Hyunsik; Choi, Eunsoo; Ko, Hyungduk; Hwang, Jinha; Park, Byoungnam (ELSEVIER SCIENCE SA, 2019)
We report enhancement of mobility and increase in mobile carrier concentration in zinc oxide (ZnO) nanocrystal (NC) field effect transistors (FETs) through the formation of a homo-junction interface using atomic layer deposition (ALD) passivation. An ultrathin ALD-ZnO passivation film deposited on a ZnO NC film not only increased the FET mobility from 4.6x10(-6) to 1.4x10(-4) cm(2)/V but also caused earlier turn-on of the ZnO NC FETs, shifting the threshold voltage from 18.9 to -4.6 V. The enhanced FET mobility and earlier turn-on in the FET are attributed to reduced localized state density on the ZnO NC surface through ALD-ZnO passivation. Passivation of the surface states mitigates carrier depletion in the ZnO NC film through oxygen adsorption on the ZnO surface. We also observed that the presence of saturation of the drain in a high drain-source voltage region depends on the ALD-ZnO passivation and its origin is discussed. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: LIGHT-EMITTING-DIODES; CHARGE-TRANSPORT; SURFACE; DEPOSITION; EFFICIENCY; BEHAVIOR; DEFECTS; DEVICES; FILMS; SIZE